2018
DOI: 10.3390/nu10080953
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vitamin D Toxicity from Overcorrection of Vitamin D Deficiency: A Review of Case Reports

Abstract: Over the past two decades, vitamin D level measurements have become some of the most frequently ordered tests in the laboratory. This increase is due to a growing awareness of widespread vitamin D deficiency and scientific data suggesting the beneficial effects of vitamin D in various diseases. A literature search was carried out in PubMed for cases reporting vitamin D intoxication and overdose. Thirteen articles were included in this review. Intoxication was severe in the reported cases. Patients presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
20

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 35 publications
(35 reference statements)
3
82
0
20
Order By: Relevance
“…An overview of VDT cases caused by vitamin D formulation or administration errors that resulted in excessive dosing confirmed that intoxication is extremely rare. However, VDT should always be considered as a differential diagnosis in patients with hypercalcemia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…An overview of VDT cases caused by vitamin D formulation or administration errors that resulted in excessive dosing confirmed that intoxication is extremely rare. However, VDT should always be considered as a differential diagnosis in patients with hypercalcemia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D intoxication is rare and usually only occurs at very high supplementation doses [109]. However, various mutations in vitamin D metabolizing enzymes that may lead to increased sensitivity to standard vitamin D supplementation or even endogenous vitamin D intoxication with hypercalcemia, hypercalciuria, and nephrocalcinosis/ chronic renal insufficiency have been described [110].…”
Section: Vitamin D Intoxication and Hypersensitivitymentioning
confidence: 99%
“…Of course, well-documented human trials examining the effect of excessive doses of vitamin D are ethically impossible so that there is a paucity of evidence regarding the exact mechanism by which vitamin D intake causes toxicity. From published reports, though, it is clear that vitamin D toxicity can occur via ingestion of over the counter products such as Soladex, that contains over 800,000 IU of vitamin D per dose [38]. Genetic disorders in which vitamin D is not normally metabolized can lead to excessive amounts of 1,25(OH)2D, despite normal intake of vitamin D [39].…”
Section: Threshold For Defining Vitamin D Excessmentioning
confidence: 99%